Proficiency affects intra- and inter-regional patterns of language control in second language processing. Issue 6 (3rd July 2019) - Grant, Angela; Li, Ping
ABSTRACT: This study examines the use of cognitive control during second language (L2) processing by adult language learners. Although cognitive control has been acknowledged as an important component of language processing for years, its conception was as a top-down mechanism of inhibition. Our functional MRI study investigated the correlates of both top-down and bottom-up control as well as semantic decision-making in a group of Spanish learners who varied in proficiency. We observed that multivariate activity patterns were better classified in high proficiency learners during the semantic decision task in regions associated with both top-down and bottom-up control. Additionally, we found that connectivity between these control regions was more organised in high than in low proficiency learners. These findings provide support for the relevance of the distinction between top-down and bottom-up control to language learning. The implications of this distinction are discussed with respect to the current theories of L2 acquisition.